Pelatihan Seni Cetak Tinggi dengan Teknik Cukil sebagai Upaya Peningkatan Kreativitas Karang Taruna di Desa Tamansuruh - Jefry Aulia Martha; Naisca Aufa Olivia; Ferdika Rosyita Andari; Mohammad Iqbal Firman Ardiansyah; Mohammad Hilfi Azra Dzikrulloh (IAI Darussalam, 2021)
Youth organizations are one of the important actors in the village development process in various fields, one of which is in the arts and culture. Tamansuruh Village is no exception, this village has a lot of arts and culture such as pencak somping, gandrung dances which are used as entertainment for villagers and painting arts. However, nowadays young people prefer western culture such as k-pop or tik tok. From that problem, the KKN team returned to their hometown to make an easy training based on local arts and culture, namely training in high print art with the cukil technique. The activity was carried out on June 29, 2021 at the Wonosari Shelter, Tamansuruh Village, while the methods used were in the preparation, implementation, and evaluation stages. Activities carried out include the preparation of tools and materials, presentation of materials and the practice of making high-quality printed works of art using the cukil technique. With this activity, it is hoped that it can increase the creativity of youth organization and can create works of art that have economic value.